If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(6p+8)+4p=-1-p
We simplify the equation to the form, which is simple to understand
-(6p+8)+4p=-1-p
Remove unnecessary parentheses
-6p-8+4p=-1-p
We move all terms containing p to the left and all other terms to the right.
-6p+4p+1p=-1+8
We simplify left and right side of the equation.
-1p=+7
We divide both sides of the equation by -1 to get p.
p=-7
| 64=2x+20 | | 4+4b=1 | | -7n-33=-8(8-3n) | | ln(x+6)=9 | | Hg(x)=2.87(24)sqrt+20.08 | | 4(2x-3)+x=9x-1-6x+19 | | 3p=-4p+7 | | -y+18=-32 | | 3r+3=-5 | | -5y+24=-1 | | n-21=-3(-4+7)+6n | | 7+4r=10 | | -3y-48=-7 | | 2.2=2n+0.2 | | 4y-35=-3 | | 55-10x=10x | | 5y-1=-11 | | (x+5)*(4x-4)=(x+1)*(x+1) | | 1820+230.25x=4813.25 | | 5x+35+55y= | | 6n-12=3x(2n-4) | | 14w=16(w+12) | | 21=8x+1-3x | | 4x+10=3+7-2x | | 8y+7=-9 | | -3j+9=-6j | | 2x+9+2x+9=180 | | 20.50x+175+289=1386.50 | | 2y+4(y-2)=8y-4(y-10) | | 2(x-a)=3(a+x) | | 10=5(2r-3) | | 12q=2q+40 |